A long-life lithium ion sulfur battery exploiting high performance electrodes1. Issue 77 (4th October 2015) - Moreno, Noelia; Agostini, Marco; Caballero, Alvaro; Morales, Julián; Hassoun, Jusef
<x xml:space="preserve">Abstract</x> A very safe, lithium ion sulfur battery operates at 2 V with capacity of 600 mA h g−1, high energy and remarkable cycle life.